Discours de haine et de radicalisation Les notions clés - Lorenzi Bailly, Nolwenn; Moïse, Claudine (Langages, 2023)
Identifying discursive features of hate speech is a complex process which could be affected by digital practices. On the one hand, it is relatively easy to analyse what we have called "discours de haine directe" (direct hate speech) which relies on three concomitant conditions: the pathemic discursive dimension, the negation of otherness and judgement speech acts (provocation, offence, threat...). But the "discours de haine dissimulée" (covert hate speech) is to be viewed from the perspective of the role played by power relations and ideologies in determining hate speech through rhetorical figures such as argument ad hominem, indirect speech acts (blame, contempt, guilt...) and the concepts of preserved ethos and "discursive memory". In this sense, data analyses also involve a critical argumentative and sociolinguistic approach to discourse. Hate speech resorts to numerous rhetorical features that need to be clarified. Based on current events, explored through argumentative or discursive analyses that illustrate the theoretical propositions developed, this book presents concepts linked to the diversity of hate speech. Among other notions, let us mention: performativity, the figure of the enemy, disqualification, gender-bias, the "fascist-sphere" or prevention. The papers, which are relatively short and echo each other, offer an insight into what is at work within hate or radicalization speech.